1994
DOI: 10.1046/j.1471-4159.1994.62062472.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐Mediated Degeneration of the Axonal Cytoskeleton in the Ola Mouse

Abstract: The C57BL/Ola (Ola) mouse is a mutant substrain in which transected axons undergo very slow Wallerian degeneration. Because axonal degradation during Wallerian degeneration is calcium dependent, we tested whether Ola axons are susceptible to calcium-mediated axonal degeneration by comparing neurofilament degradation between Ola and C57BL/6 mice in sciatic nerve explants. Using immunoblot analysis of neurofilament degradation and electron microscopy we found that as in normal axons, axonal degeneration in the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…39 For example, channel-mediated influx of extracellular Ca 2+ is essential for the initiation of acute axonal degeneration (AAD), for Ca 2+ activated serinethreonine protease calpain breakdown of tubulin of axonal microtubules, spectrin of the subaxolemma cytoskeleton and neurofilaments, 53, 54, 40 disruption of mitochondrial structure and function leading to opening of the mitochondrial membrane transition pore 55,56 and activation of calpain in the distal axon after axotomy. 57,40 The mode of loss of axons from the proximal part of the left optic tract differed from that reported previously in the proximal segment of the injured optic nerve. 14 It is suggested that a reason is that the optic tract contains axons from parts of two retinae while the optic nerve contains axons from a single retina.…”
Section: Discussionmentioning
confidence: 60%
“…39 For example, channel-mediated influx of extracellular Ca 2+ is essential for the initiation of acute axonal degeneration (AAD), for Ca 2+ activated serinethreonine protease calpain breakdown of tubulin of axonal microtubules, spectrin of the subaxolemma cytoskeleton and neurofilaments, 53, 54, 40 disruption of mitochondrial structure and function leading to opening of the mitochondrial membrane transition pore 55,56 and activation of calpain in the distal axon after axotomy. 57,40 The mode of loss of axons from the proximal part of the left optic tract differed from that reported previously in the proximal segment of the injured optic nerve. 14 It is suggested that a reason is that the optic tract contains axons from parts of two retinae while the optic nerve contains axons from a single retina.…”
Section: Discussionmentioning
confidence: 60%
“…The retraction involves creation of densely packed NF domains (McHale et al,1995) initiated by proteolysis of the NF sidearms (Hall and Lee,1995), and is an active process, since it is greatly slowed in the isolated spinal cord (Zhang et al,2005). NF proteins are degraded by calpains (Schlaepfer and Hasler,1979; Pant et al,1982; Zimmerman and Schlaepfer,1982; Glass et al,1994). The mechanism for this effect is unknown but reduction of axon terminal retraction has been seen in porcine photoreceptors exposed in vitro to either 8‐(4‐chlorophenylthio)‐cAMP or forskolin (Khodair et al,2005).…”
Section: Discussionmentioning
confidence: 99%
“…Culturing neurons in a reduced calcium environment by switching to low Ca 2+ media (below 200uM) or chelating external Ca 2+ with EGTA robustly delays axon degeneration for 4 d after axotomy, whereas adding Ca 2+ ionophores is sufficient to revert the protective phenotype and induce degeneration in uninjured neurites (Schlaepfer and Bunge, 1973; George et al, 1995). Similar to AAD, the Ca 2+ -dependent protease calpain is also activated in the distal axons from rising Ca 2+ levels after axotomy (Glass et al, 2002); however, chemically inhibiting calpain activity only delays axon degeneration for 12–24 h in vitro (Glass et al, 1994; Wang et al, 2000). The significantly weaker axonal protection from calpain inhibition alone compared with Ca 2+ chelation (Finn et al, 2000; Zhai et al, 2003) suggests that additional Ca 2+ -dependent proteases or pathways mediate the cytoskeletal breakdown in Wallerian degeneration.…”
Section: Phase Ii: Latency In the Distal Axonmentioning
confidence: 99%
“…Events similar to Wallerian axon degeneration also occur in genetic mutants such as pmn that are impaired in axonal transport (Martin et al, 2002), where there is an absence of direct trauma and where the source of Ca 2+ influx into the axon is not apparent (Coleman, 2005). Moreover, exogenous addition of Ca 2+ is sufficient to abolish WldS-mediated axonal protection (Glass et al, 1994), indicating that the calcium-dependent activities in the axon are downstream of molecular components that suppress the activation of Wallerian degeneration. Thus, although Ca 2+ signaling is clearly critical for axonal degradation, more upstream cellular processes likely trigger the increased intra-axonal Ca 2+ levels by promoting channel-mediated influx or modulating intracellular Ca 2+ buffering and release, or both, while subsequent Ca 2+ -dependent proteolytic events mediate the physical destruction of the axon.…”
Section: Phase Ii: Latency In the Distal Axonmentioning
confidence: 99%